On the main stages of the history of intra-articular therapy - L. Punzi; G. Pasero; P. Marson; G. Zanchin (PAGEPress Publications, 2011)
In this review the main stages in the history of intra-articular therapy of the rheumatic diseases are summarized. The first approach to such a local treatment has been likely performed in 1792 by the French physician Jean Gay, who injected in a swelling knee the "eau du Goulard" (Goulard's water), namely a mixture based on lead compounds. In the XIX century iodine derivatives have been mainly applied as an intra-articular treatment. In the XX century, before the wide use of intra-articular corticosteroids, chiefly due to the Joseph Lee Hollander's experiences, a variety of drugs has been employed, including cytostatics and sclerosing substances. A further important stage has been synoviorthesis, by using specific radionuclides, that would actually represent an anti-synovial treatment. In the last years a spread use of intra-articular hyaluronic acid, particularly in osteoarthritis, has been recorded, with the aim to warrant articular viscosupplementation. Future of intra-articular treatment should be represented by the biological drugs, i.e., anti-TNF, but it is still untimely to define the exact role of such a local treatment of arthritis.